2019
DOI: 10.1038/s42003-019-0608-y
|View full text |Cite
|
Sign up to set email alerts
|

Early stage prion assembly involves two subpopulations with different quaternary structures and a secondary templating pathway

Abstract: The dynamics of aggregation and structural diversification of misfolded, host-encoded proteins in neurodegenerative diseases are poorly understood. In many of these disorders, including Alzheimer’s, Parkinson’s and prion diseases, the misfolded proteins are self-organized into conformationally distinct assemblies or strains. The existence of intrastrain structural heterogeneity is increasingly recognized. However, the underlying processes of emergence and coevolution of structurally distinct assemblies are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 60 publications
2
36
0
Order By: Relevance
“…This approach has been unsuccessfully attempted in the case of LA21K fast . This fail could be due to the weakness of the suPrP A :suPrP B complex, as previously observed [20]. Indeed, size exclusion chromatography analysis of the 127S suPrP A :suPrP B complex revealed that this last is highly labile and can be observed only in conditions where the concentration of suPrPA and suPrPB were high.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…This approach has been unsuccessfully attempted in the case of LA21K fast . This fail could be due to the weakness of the suPrP A :suPrP B complex, as previously observed [20]. Indeed, size exclusion chromatography analysis of the 127S suPrP A :suPrP B complex revealed that this last is highly labile and can be observed only in conditions where the concentration of suPrPA and suPrPB were high.…”
Section: Discussionmentioning
confidence: 52%
“…It implicates interactions between structurally distinct PrP Sc subsets in order to create a new structural information absent in each individual PrP Sc population and leading to heterologous PrP C integration. During the early stage of prion replication, we showed that two sets of structurally distinct PrP Sc assemblies are generated, in fractions 1-5 and 10-18 [20]. These sets are defined by their elementary subunit [13] as suPrP A and suPrP B , respectively [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations